2006
DOI: 10.1007/s11517-006-0038-0
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear additive autoregressive model-based analysis of short-term heart rate variability

Abstract: In this contribution we test the hypothesis that nonlinear additive autoregressive model-based data analysis improves the diagnostic ability based on short-term heart rate variability. For this purpose, a nonlinear regression approach, namely, the maximal correlation method is applied to the data of 37 patients with dilated cardiomyopathy as well as of 37 age- and sex-matched healthy subjects. We find that this approach is a powerful tool in discriminating both groups and promising for further model-based anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…44 Our studies support the view that there is a strong interaction between the central nervous sleep regulation and the autonomous nervous system regulation. Until today it is not possible to distinguish those patients with sleep apnea which do develop arterial hypertension and congestive heart failure and those who do not.…”
Section: Discussionsupporting
confidence: 84%
“…44 Our studies support the view that there is a strong interaction between the central nervous sleep regulation and the autonomous nervous system regulation. Until today it is not possible to distinguish those patients with sleep apnea which do develop arterial hypertension and congestive heart failure and those who do not.…”
Section: Discussionsupporting
confidence: 84%
“…These approaches on the one hand aim at modeling one or more regulation processes, and on the other hand provide model parameters which should be used to answer clinically relevant questions. In this tutorial we have introduced an approach which is very promising in data-driven modeling and modelbased data analysis [Wessel et al, 2000b;Wessel et al, 2004a;Wessel et al, 2004b;Wessel et al, 2006]. We have found that the maximal correlation method is a powerful tool for medical data analyses and for solving mechanical engineering problems.…”
Section: Discussionmentioning
confidence: 99%
“…This makes the result less sensitive to the data distribution. The maximal correlation and optimal transformation approach have recently been applied to nonlinear dynamical systems especially to model river flow data [Chen & Tsay, 1993], to identify delay in lasers [Voss & Kurths, 1997] and partial differential equations in fluid dynamics , to predict thermal displacements in modular tool systems [Wessel et al, 2004a;Wessel et al, 2004b] and to medical data analyses [Wessel et al, 2000b;Wessel et al, 2006]. A more general review on nonlinear system identification is given in .…”
Section: Nonlinear Model Based Data Analysismentioning
confidence: 99%
“…Atrial fibrillation has been characterized with CVRR and CVdRR [60]. In patients with recent myocardial infarction VarIndex was found to be useful [61], PolVar20 with different thresholds was used in risk stratification for acute myocardial infarction [62], for identifying congestive heart failure [63], and for forecasting ventricular tachycardia [51].…”
Section: Other Indices and Their Short Term Usementioning
confidence: 99%